Experimental methods of identifying sound sources on a machine - CROCKER, Malcolm J. (Archives of Acoustics, 1983)
There are many existing methods to identify noise sources and paths and some newer methods have also been recently developed. Several existing techniques have been used to identify noise sources on machines for many years. None are completely satisfactory. They are usually inaccurate, expensive, time consuming and often need special acoustic facilities. The most commonly used technique is perhaps the selective-wrapping or lead-wrapping approach. Recently, fast Fourier transform (RFT) minicomputers have become widely available and theory has been published for the calculation of acoustic intensity from two simultaneously measured signals. Two new techniques have been investigated by a number of research workers. These two techniques are: the surface intensity approach (microphone-accelerometer) and the acoustic intensity approach (two-microphone). These two new techniques can be used to study sound sources and sound paths and will be discussed in this paper in some detail. The paper begins with a brief review of some of the earlier methods, continues with a description of other methods of noise source identification and concludes with a discussion of the newer intensity and coherence techniques to identify machinery noise sources and paths.